Microhistory and History of Education “From Below”: Epistemological and Methodological Issues - Manolis Kounalakis (Language, Literature and Education: Research Updates Vol. 5, 2025)
This chapter examines the development of the microhistorical paradigm in the theory of historiography and, more specifically, refers to the penetration of this methodology in the field of the history of education. It is a theoretical overview of the field as far as possible. First, the origins of the emergence of the micro-historical paradigm by historians in the period 1960 to 1970 are discussed. The key theoretical principles influencing the emergence of micro-historical methodology are then listed with a focus on the theory of interpretive anthropology, the linguistic turn and power relations. It then discusses protagonists of the implementation of microhistorical methodology mainly in Italian historiography as well as the influences of Italian historians abroad. This is followed by the listing of some key features concerning the implementation of the microhistorical approach to historical research. The major innovation of this chapter focuses on the connection that is made between the field of the history of education and bottom-up historical research methodology. For this reason, key references are made to the themes in the history of education around which this methodology can be applied. In the conclusions of the chapter, it is suggested that this methodology can be used through the co-examination of archival materials that usually relate to micro-historical research (e.g diaries, autobiographies, oral histories, etc.) together with evidence that would otherwise not be considered in such a perspective.